2018
DOI: 10.3847/1538-4357/aaad09
|View full text |Cite
|
Sign up to set email alerts
|

Seeds of Life in Space (SOLIS). III. Zooming Into the Methanol Peak of the Prestellar Core L1544*

Abstract: Corresponding author: Anna Punanova punanova@mpe.mpg.de * This work is based on observations carried out under project number L15AA with the IRAM NOEMA Interferometer and on observations carried out with the IRAM 30 m telescope. IRAM is supported by INSU/CNRS (France), MPG (Germany) and IGN (Spain).

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 58 publications
4
44
1
1
Order By: Relevance
“…However, while the methanol peak in L1544 is located at ∼4000 au from the core center, the methanol blob in L1521F is found at roughly ∼1000 au. At this distance, methanol is clearly depleted in L1544 (Bizzocchi et al 2014;Vastel et al 2014;Jiménez-Serra et al 2014;Punanova et al 2018) due to the high density and low temperatures found at this distance in the core. Crapsi et al (2004) used the 1.2 mm continuum data of L1521F from the IRAM-30 m to estimate the density distribution under the assumption of spherical symmetry.…”
Section: On the Nature Of The Ch 3 Oh Blob In L1521fmentioning
confidence: 89%
See 2 more Smart Citations
“…However, while the methanol peak in L1544 is located at ∼4000 au from the core center, the methanol blob in L1521F is found at roughly ∼1000 au. At this distance, methanol is clearly depleted in L1544 (Bizzocchi et al 2014;Vastel et al 2014;Jiménez-Serra et al 2014;Punanova et al 2018) due to the high density and low temperatures found at this distance in the core. Crapsi et al (2004) used the 1.2 mm continuum data of L1521F from the IRAM-30 m to estimate the density distribution under the assumption of spherical symmetry.…”
Section: On the Nature Of The Ch 3 Oh Blob In L1521fmentioning
confidence: 89%
“…In this context, Tafalla et al (2004) suggest that the ring-like morphology for CH 3 OH in prestellar cores is due to depletion of C-bearing species close to the dust emission peak. A189, page 3 of 11 A&A 635, A189 (2020) Interestingly enough, Punanova et al (2018) has observed a centrally peaked emission fragment for CH 3 OH around the center of the L1544 prestellar core and inferred that the methanol emission could arise from an accretion shock. Such structures are likely the result of dynamical gas interaction such as fragmentation (see Tokuda et al 2014).…”
Section: Methanol Channel Emission Mapsmentioning
confidence: 99%
See 1 more Smart Citation
“…As for CH 3 OH, it is also a species that has been found in PDRs as well as in molecular clouds (e.g. Leurini et al 2010;Guzmán et al 2013;Cuadrado et al 2017;Punanova et al 2018). Thus, an important contribution from the parental molecular cloud or from the surrounding PDR may occur when observing those molecules with single-dish telescopes.…”
Section: Introductionmentioning
confidence: 98%
“…The situation may not be that simple in this specific core. These are interferometric observations of methanol emission presented by [23], and they show that methanol emission is observed on one side of the core. This may imply that there is some illumination from this side.…”
mentioning
confidence: 65%